Toll-like receptor signaling activation by Entamoeba histolytica induces beta defensin 2 in human colonic epithelial cells: its possible role as an element of the innate immune response. - Jorge-Tonatiuh; Victor M Téllez-López; M del Carmen Domínguez-Robles; Mineko Shibayama-Salas; Isaura Meza (Public Library of Science (PLoS), 2013)
BACKGROUND: Entamoeba histolytica, a protozoan parasite of humans, produces dysenteric diarrhea, intestinal mucosa damage and extraintestinal infection. It has been proposed that the intestinal microbiota composition could be an important regulatory factor of amebic virulence and tissue invasion, particularly if pathogenic bacteria are present. Recent in vitro studies have shown that Entamoeba histolytica trophozoites induced human colonic CaCo2 cells to synthesize TLR-2 and TLR-4 and proinflammatory cytokines after binding to the amebic Gal/GalNac lectin carbohydrate recognition domain. The magnitude of the inflammatory response induced by trophozoites and the subsequent cell damage were synergized when cells had previously been exposed to pathogenic bacteria. METHODOLOGY/PRINCIPAL FINDINGS: We show here that E. histolytica activation of the classic TLR pathway in CaCo2 cells is required to induce β defensin-2 (HBD2) mRNA expression and production of a 5-kDa cationic peptide with similar properties to the antimicrobial HBD2 expressed by CaCo2 cells exposed to enterotoxigenic Escherichia coli. The induced peptide showed capacity to permeabilize membranes of bacteria and live trophozoites. This activity was abrogated by inhibition of TLR2/4-NFκB pathway or by neutralization with an anti-HBD2 antibody. CONCLUSIONS/SIGNIFICANCE: Entamoeba histolytica trophozoites bind to human intestinal cells and induce expression of HBD2; an antimicrobial molecule with capacity to destroy pathogenic bacteria and trophozoites. HDB2's possible role as a modulator of the course of intestinal infections, particularly in mixed ameba/bacteria infections, is discussed.